2018
DOI: 10.1111/aji.13055
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukins in preeclampsia: A comprehensive review

Abstract: Preeclampsia is a multi‐system hypertensive disorder of pregnancy, with significant rates of maternal and neonatal morbidity. It represents a major cause of preterm birth, as definitive treatment demands fetal delivery. Although its pathophysiology is complicated, placental hypoxia and endothelial dysfunction constitute established pathogenetic steps of the disease. Inflammation is considered to be a crucial mediator of preeclampsia process, as an imbalance between TH1, TH2, and TH17 immune responses is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 216 publications
0
39
0
1
Order By: Relevance
“…Moreover, acute atherosis has been linked to increased oxidative stress and lipid content in the decidua of preeclamptic women . Oxidative stress is also implicated in the pathophysiology of preeclampsia and fetal growth restriction . Hence, we proposed that macrophages are implicated in the mechanisms leading to oxidative stress, and therefore, obstetrical disease (ie, acute atherosis).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, acute atherosis has been linked to increased oxidative stress and lipid content in the decidua of preeclamptic women . Oxidative stress is also implicated in the pathophysiology of preeclampsia and fetal growth restriction . Hence, we proposed that macrophages are implicated in the mechanisms leading to oxidative stress, and therefore, obstetrical disease (ie, acute atherosis).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of preeclampsia is complex and remains still under investigation. It is hypothesized that poor trophoblast invasion and deficient spiral artery remodeling lead to placental ischemia‐reperfusion injury 4 and the release of various angiogenic, 5 oxidative, 6 and inflammatory 7 mediators into maternal circulation, promoting generalized endothelial dysfunction, increased vascular reactivity, and activation of the coagulation cascade 8 . Risk stratification is essential in order to identify the subpopulation of pregnant women that would benefit from preventive measures early in the course of gestation, especially the administration of aspirin 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Most APO can trace their origins to placenta, especially to placental inflammation/infection . Pre‐eclampsia and fetal growth restriction are rooted in defects of early placental development and later placental inflammation (the two‐stage model) . Stillbirth and fetal growth restriction are associated with placental inflammation due to infectious or noninfectious causes .…”
Section: Introductionmentioning
confidence: 99%
“…9 Preeclampsia and fetal growth restriction are rooted in defects of early placental development and later placental inflammation (the two-stage model). 9,10 Stillbirth and fetal growth restriction are associated with placental inflammation due to infectious or noninfectious causes. 9 A recent morphological study showed that inflammation/infection and malperfusion were the two most common pathological changes in the placentas of preterm birth.…”
Section: Introductionmentioning
confidence: 99%